Pengembangan Ekonomi Dan Lembaga Keuangan Melalui Pendekatan Filsafat Ekonomi Islam - Ahmad Ali Kamal; Shalahudin Habibullah; Ummi Kaltsum Karunianing; Desta Marta Nita; Madnasir (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2026)
Contemporary Islamic economics literature (2022–2025) tends to be dominated by analyses of technical compliance in Islamic fintech products and sukuk. However, studies highlighting the gap between compliance formality and the substantive achievement of maqasid al-shari’ah—especially regarding distributive justice—remain very limited. This research offers novelty by reconstructing the philosophical foundations of Islamic Financial Institutions (IFIs) to shift the focus from formal legality toward real social impact. Using an integrative-critical literature review method, this study synthesizes more than 25 accredited sources through thematic analysis to evaluate the regulations and practices of IFIs in Indonesia. The results show that without the integration of the amanah philosophy and the ta’lil al-ahkam approach, financial products are often trapped in